Green Sintesis Dan Karakterisasi Material Nanokomposit TiO2/CuO Menggunakan Ekstrak Daun Wedelia trilobata (L.) - Sarimanella, Stefhanie B.; Titahena, Apriliska; Latununuwe, Altje; Huliselan, Estevanus Kristian (Pattimura University, 2022)
TiO2/CuO nanocomposite has been successfully synthesized using Wedelia trilobata (L.) leaf extract with TiCl3 and Cu(NO3)2 3H2O as precursors. The material formed was then characterized by scanning electron microscopy (SEM) to determine the shape and size and then energy dispersive X-ray (EDX) characterization to determine the atomic composition contained in this nanocomposite material. The results of SEM and EDX show that the material is spherical in shape and has an average size of 42 nm. The composition of TiO2 is 73.38% and CuO is 4.32%. Furthermore, the sample is characterized by X-ray diffraction (XRD) in which the diffraction peaks are at angles of 2 theta, 25.646° and 47.511° indicating TiO2 nanoparticle. Meanwhile, peaks are at 38.367° and 74.379° indicate CuO nanoparticle. Determination of the energy band gap of the material using the results of ultraviolet visible (UV-Vis) is 3.5 eV. Measurement of magnetic properties using VSM equipment. Based on the hysteresis curve, the TiO2/CuO nanocomposite material has diamagnetic properties and is a soft magnet material.